Profile of livestock farmers from Tocantins and green cattle breeding - Dall’Agnol, Mateus; Silva, Gildemberg da Cunha; Bastos, Renato de Oliveira; Vieira Junior, Jaime do Espirito Santo; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The purpose of this article is to study and evaluate the profile of ranchers of beef cattle located in the State of Tocantins. Applied in a first moment a closed questionnaire focused on charting the social profile of the ranchers. Then we applied a questionnaire with open questions in which the ranchers issued their opinion on economic activity, logistics, environmental indicators, animal, pasture and technology. It was adopted the method of saturation to analyze qualitative data, discursive. The study was divided into two steps: data collection, with semistructured interviews with ranchers in the three regions of the State (North, central and South). In another step they have tabbed the data obtained in the collection and analyzed the profiles of ranchers highlighting its specificities. For the analysis, the ranchers were separated into 3 groups: small, medium and large ranchers. All ranchers analyzed are cattle breeders, who sell directly or indirectly to refrigerators. This article identifies the cattleman profile state of Tocantins and the Green supply chain management system and its competitive edge in the creation of cattle.